Rescuing migrants in Libya: The political economy of state responses to migration crises. The case of Ghana - George M. Bob-Milliar (Danish Institute for International Studies (DIIS), 2012)
This paper has two main aims. First, it explores the return of young Ghanaian migrants from Libya following the uprising in 2011. Secondly, the paper is interested in the role state agencies played in the repatriation and resettlement of returnees. Migrants from some 120 countries living in Libya were directly affected by the conflict. The breakdown of law and order saw Ghanaian migrants become targets when the rebels accused the Gaddafi regime of recruiting mercenaries from Sub-Saharan Africa to help put down the rebellion. The conflict brought up the issue of migration management in times of crisis. What was the response of the government of Ghana to its citizens caught up in the crisis? Through a qualitative study of official documents, newspaper reports and in-depth interviews, the paper discusses migration and state responses within a political economy perspective. It posits that Ghanaian migration patterns show no significant difference between the various time periods. However, the characteristics of migrants have changed. Thus, it appears the country has witnessed an increased emigration of young people during the last two decades.
Keywords: 300